The Influence of Leadership Style, Employee Competence and Career Development on Employee Performance with OrganizationalCommitment as Intervening at PT Pelindo Multi Terminal - Nofrizal; M. Chaerul Rizky; M. Toyib Daulay (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of leadership style, employee competence, and career development on employee performance with organizational commitment as an intervening variable in PT Pelindo Multi Terminal. This study uses a quantitative approach with causal associative research. The research population is all employees of PT Pelindo Multi Terminal totaling 40 people, with sampling techniques using saturated samples so that the entire population is used as respondents. Data was collected through a questionnaire using the Likert scale and analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) with the help of SmartPLS software. The results showed that leadership style, employee competence, and career development had a positive and significant effect on organizational commitment with path coefficient values of 0.418 (p = 0.000), 0.491 (p = 0.000), and 0.268 (p = 0.023), respectively. Employee competencies have the strongest influence on organizational commitment. However, this study found that the three independent variables did not have a significant effect directly on employee performance, with p-values of 0.614, 0.309, and 0.240, respectively for leadership style, employee competence, and career development. Another important finding was that organizational commitment had no significant effect on employee performance (β = 0.302; p = 0.238). Indirect influence analysis shows that organizational commitment does not successfully mediate the relationship between leadership style, employee competence, and career development to employee performance. All mediation pathways showed insignificant results with p-values ranging from 0.262 to 0.293.